Baseline Scenario of Carbon Footprint of Polyester T-Shirt (Journal of Fiber Bioengineering and Informatics, 2018)
Environmental sustainability is a vital issue in the clothing industry due to a large percentage of greenhouse gas (GHG) emissions from clothing manufacturing to consumption. The main GHGs are carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), hydro fluorocarbons (HFCs), per fluorocarbons (PFCs) and sulphur hexafluoride (SF6). Carbon dioxide is considered as the most significant greenhouse gas. The carbon footprint (CFP) of clothing supply chain reflects the GHG emissions throughout the life cycle of a product or activity, and CFP assessment is an important approach to assess GHG emissions. Polyester is one of the most widely used synthetic fibres in the world, but it is produced from non-renewable resources. In this study, a life cycle assessment (LCA) of a polyester T-shirt imported to Australia from China has been undertaken to examine the processes which cause GHG emissions across the life cycle. The results of the baseline model showed that consumer use phase contributes the highest CFP 30.35%, and second highest contributor is polyester fibre production process. Within the production phase, spinning is the highest contributor of CFP due to high electric energy demand. Within the consumer use phase, CFP is dominated by the washing process. The results of the model can be considered reliable comparing with other related studies.